Attitudes of people towards same-sex couples raising children in South Africa: an analysis of the demographic and socio-economic determinants - Nongena, Pelisa (My University, 2020)
Background: It is widely recognized that the institutions of marriage and family have been undergoing transformation, especially during the second half of the twentieth century. The increase in the number of same-sex marriages and parents is soaring in the African continent. Changes in laws and developments in reproductive technologies have made it possible for same-sex partners to become parents in many African countries, including South Africa. However, the practice remains highly stigmatized by the general public. Methods: This study used secondary statistics acquired from the 2016 SA Social Attitude Survey. The Survey consisted of 3500 male and female residents of South Africa aged 16 years and above. However, the analytic sample size used in this study was 2679respondents who were citizens of South Africa, and the remaining 821non-citizens were dropped. The Descriptive variables used in the study include age, sex, race, religious affiliation, educational attainment, employment status, marital status, income, satisfaction with health, access to TV, and access to radio. The outcome variable was attitudes towards same-sex couples raising children in South Africa. A chi square test and multinomial logistic regression was carried out to determine the socio-demographic factors associated with attitudes toward same-sex couples raising children in South Africa. The multinomial logistic regression was divided into five models, the first one showing socio demographic characteristics, second one outlining socio-economic characteristics and a third one showing success to media. The fourth model shows access to media and the fifth one is an all-inclusive model. Results: The study found that 56% of the respondents agree that same-sex couples must be allowed to raise children in South Africa. Results from the multinomial logistic regression all-inclusive model indicate that the only sociodemographic characteristics significantly associated with attitudes are Race, type of residence and access to TV. Conclusion: These findings are expected to inform policy interventions and programs such as the Lesbian Gay Bisexual Transgender Intersex and Questioning National task (LGBTQI+IQ NTT), the Housing and Urban Development (HUD) and IMPACT-which are aimed at reducing same-sex stigma and promote childcare
A research report submitted to the Schools of Public Health and Social Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the award of the degree of Master of Arts in Health Demography, 2020